Flipped Presentation of Authentic Audio-Visual Materials: Impacts on Intercultural Sensitivity and Intercultural Effectiveness in an EFL Context - Khabir, Masoud; Jabbari, Ali Akbar; Razmi, Mohammad Hasan (Frontiers in Psychology, 2022)
Utilizing a pre-experimental pre-test post-test design, this study investigated the effect of an authentic audio-visual American sitcom (Friends) on the intercultural sensitivity (ICS) and intercultural effectiveness (ICE) of a sample of male and female upper-intermediate English students. To this aim, 34 Iranian EFL students were selected through convenient non-random sampling. In order to assure the participants' homogeneity in English proficiency, the selected students were given the Oxford Quick Placement Test prior to the intervention. Over a 10-week period, the participants were presented with nearly 30-min-long episodes of Friends in a flipped context, two episodes every week uploaded to the accompanying website. An online 10-item quiz on the day of watching and a next-day meeting were held. During the online discussion meetings, the participants discussed cultural questions tailored to the aims of the study. The required data were collected through the administration of the intercultural sensitivity scale (ISS) and intercultural effectiveness scale (IES) in pre- and post-test assessments. The analyses of the data indicated that both ICS and ICE improved significantly during the intervention. However, ICS indicated more improvement. In addition, a semi-structured interview was administered to the participants to examine their perception of the flipped classroom experience. Having analyzed the data using MAXQDA 2020, some significant themes emerged which are reported. On the whole, the participants portrayed positive attitudes toward using technology in flipped classes. The educational and practical implications are discussed.